A Novel Carbon‐Encapsulated Cobalt‐Tungsten Carbide as Electrocatalyst for Oxygen Reduction Reaction in Alkaline Media. Issue 3 (8th May 2013) - Zhong, G.; Wang, H.; Yu, H.; Peng, F.
Abstract Carbon‐encapsulated cobalt‐tungsten carbides (CoWC@C) were synthesized by reduction and carbonization method and used as the electrocatalyst for oxygen reduction reaction (ORR) in direct methanol fuel cells. The as‐prepared samples were characterized by transmission electron microscope, X‐ray diffraction, and X‐ray photoelectron spectroscopy. The results show that CoWC@C consists of outer layer carbon and internal Co3W3C, WC, and Co. The cyclic voltammetry results show that CoWC@C has high ORR activity, long‐term durability, and good methanol‐tolerant performance. It is revealed that the main active phase for ORR of CoWC@C is Co3W3C, and the outer layer carbon plays the role in improving the durability of the catalyst.